349 COVID Induced Acute Ischaemic Limb. (12th October 2021) - Shah, B; Kedrzycki, M
Abstract: The coronavirus pandemic has overwhelmed healthcare systems worldwide, with more than 40 million affected and 1 million deaths. In addition to the typical symptoms, less clinically obvious was the underlying hypercoagulable state, termed COVID-19 associated coagulopathy (CAC). The exact mechanism of CAC is unknown, but it is suspected to involve all three aspects of Virchow's Triad: endothelial injury, stasis, and a hypercoagulable state. Here we report the case of a woman in her 60's who was admitted with COVID-19 and developed CAC with subsequent complications. She presented with a 3-day history of fevers, severe shortness of breath, and cough. Past medical history was significant for hypertension, poorly controlled insulin dependant diabetes, and obesity. She was admitted with COVID induced type 2 respiratory failure (pO2 of 5.5 on 15L), DKA (ketones 2.1), AKI (Cr 163), and a hypercoagulable state (D-dimer >20 000). She was intubated and commenced on an insulin sliding scale, therapeutic anticoagulation, and antibiotics. On day 2 she became anuric, with CT-angio demonstrating thrombus extending from renal arteries down to the right popliteal artery. She underwent an embolectomy and 4 compartment fasciotomy and was started on renal replacement therapy. Unfortunately, her leg was not deemed viable, and due to persistent hyperkalaemia required amputation 2 days later. She continued to deteriorate despite maximal multiple organ support and was palliated 15 days later. CAC can have life-threatening sequelae, and patients with COVID-19 infection should be commenced on anticoagulation upon diagnosis.